Hydrophobically modified chitosan nanoliposomes for intestinal drug delivery - Zariwala MG (Dove Medical Press, 2018)
M Gulrez Zariwala,1 Harshada Bendre,2 Anatoliy Markiv,3 Sebastien Farnaud,4 Derek Renshaw,4 Kevin MG Taylor,2 Satyanarayana Somavarapu2 1Faculty of Science and Technology, University of Westminster, London, UK; 2Department of Pharmaceutics, University College London School of Pharmacy, London, UK; 3Faculty of Life Sciences and Medicine, King’s College London, London, UK; 4Faculty of Health and Life Sciences, Coventry University, Coventry, UK Background: Encapsulation of hydrophilic drugs within liposomes can be challenging. Methods: A novel chitosan derivative, O-palmitoyl chitosan (OPC) was synthesized from chitosan and palmitoyl chloride using methane-sulfonic acid as a solvent. The success of synthesis was confirmed by Fourier transform infra-red (FT-IR) spectroscopy and proton NMR spectroscopy (H-NMR). Liposomes encapsulating ferrous sulphate as a model hydrophilic drug for intestinal delivery were prepared with or without OPC inclusion (Lipo-Fe and OPC-Lipo-Fe). Results: Entrapment of iron was significantly higher in OPC containing liposomes compared to controls. Quantitative iron absorption from the OPC liposomes was significantly higher (1.5-fold P<0.05) than free ferrous sulphate controls. Qualitative uptake analysis by confocal imaging using coumarin-6 dye loaded liposomes also indicated higher cellular uptake and internalization of the OPC-containing liposomes. Conclusion: These findings suggest that addition of OPC during liposome preparation creates robust vesicles that have improved mucoadhesive and absorption enhancing properties. The chitosan derivative OPC therefore provides a novel alternative for formulation of delivery vehicles targeting intestinal absorption. Keywords: gut delivery, intestinal absorption, Caco-2, ferrous sulfate